2021
DOI: 10.1038/s41598-021-02830-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic optimization of visible light-induced crosslinking conditions of gelatin methacryloyl (GelMA)

Abstract: Gelatin methacryloyl (GelMA) is one of the most widely used photo-crosslinkable biopolymers in tissue engineering. In in presence of an appropriate photoinitiator, the light activation triggers the crosslinking process, which provides shape fidelity and stability at physiological temperature. Although ultraviolet (UV) has been extensively explored for photo-crosslinking, its application has been linked to numerous biosafety concerns, originated from UV phototoxicity. Eosin Y, in combination with TEOA and VC, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 59 publications
2
40
0
Order By: Relevance
“…In another study, the effects of UV light on human MSCs photoencapsulated in GelMA were studied. The results showed that upon the induction of UV light (490–510 nm) with an intensity of 20 mW/cm 2 , good cell viability (>75%) was maintained after 4 min of light exposure with a 3% reduction after 10 min 38 . Our results confirmed a similar behavior, as cell viability was preserved for UV-exposed samples exposed <3 min to an intensity of 1 mW/cm 2 at 10 cm from the source based on the Live/Dead assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the effects of UV light on human MSCs photoencapsulated in GelMA were studied. The results showed that upon the induction of UV light (490–510 nm) with an intensity of 20 mW/cm 2 , good cell viability (>75%) was maintained after 4 min of light exposure with a 3% reduction after 10 min 38 . Our results confirmed a similar behavior, as cell viability was preserved for UV-exposed samples exposed <3 min to an intensity of 1 mW/cm 2 at 10 cm from the source based on the Live/Dead assay.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of UV light on cell-hydrogel photopolymerization and cell viability have been widely reported 3,[35][36][37][38] . For instance, Lin et al 37 showed that endothelial colony-forming cells (ECFCs) and mesenchymal stem cells (MSCs) remained viable (>93%) for up to 120 s and were only negatively affected after 300 s of UV light exposure (7.5 mW/cm 2 ).…”
Section: Ssaw-patterning Of Stem Cells Enhances Cell Viability Metabo...mentioning
confidence: 99%
“…Therefore, our working range of UV light exposure was deemed sufficiently safe. Alternatively, GelMA can be formulated to form a hydrogel with visible light-responsive photoinitiators to eliminate the usage of UV light 59 . However, the crosslinking time using visible light is significantly longer than UV light 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our working range of UV light exposure was deemed sufficiently safe. Alternatively, GelMA could be formulated to form a hydrogel with visible light-responsive photoinitiators to eliminate the usage of UV light 87 , although the crosslinking time would be significantly longer than with UV light 88 . Also, UV light illumination could be used through a fiber-optic system together with a catheter, as we previously showed that with a photocurable polymer patch to fix septal defects in the beating hearts of pigs 89 .…”
Section: Discussionmentioning
confidence: 99%
“…GelMA crosslinking occurs in the presence of photoinitiators and the irritation of visible or ultraviolet (UV) light matching the photoinitiators ( Figure 1A ). Common photoinitiators compatible with biological applications are Irgacure 2959 (for UV light) and Lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP; for visible light; absorbance at 400 nm) ( Sharifi et al, 2021 ).…”
Section: Synthesis and Preparation Of Gelatin Methacrylatementioning
confidence: 99%